ANALISIS IMPLIKATUR PERCAKAPAN DALAM TUTURAN FILM LASKAR PELANGI - Yessinta Yulianti; Asep Purwo Yudi Utomo (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2020)
Implications of conversation are pragmatic implications that arise as a result of violating the principle of conversation in a speech. Implications of conversation often occur in a speech, one of them in the film. Laskar Pelangi is the fourth best-selling film with a total audience of 4.6 million people. As a film that is still often screened, there may be conversational implicature in the film's utterances. This study aims to describe the form of conversational implicature in the Laskar Pelangi film and explain the process of establishing conversational implicature as a result of violating the principle of cooperation in the Laskar Pelangi film. The research approach is a pragmatic approach and a qualitative descriptive approach. Research data in the form of fragments of speech are categorized in the form of conversational implicature and occur due to violations of the principle of cooperation. The data source of this research is a fragment of speech in the film Laskar Pelangi. In this study, the method used, namely refer to the method. The technique used is observation and note taking. The data that has been collected is then analyzed through three stages of the flow model, namely data reduction, data presentation, and data verification. Presentation of the results of data analysis in an informal form. From 9 data found, including 3 violations of quantity maxim, 1 violation of quality maxim, 4 violations of relevance maxim, and 1 violation of maxim of manner. From this research, it is expected to find implicit meaning in a film related to real life.